The Plagiarism Polyconundrum - Bethany, Reine D. (Journal of International Students, 2016)
Plagiarism hinders student success because it shortcuts genuine writing practice and incurs penalties when discovered. Although students are aware of its potential consequences, plagiarism continues. This article reflects on the polyconundrum of empathizing with the many hindrances to student writing while deploying strategies to reduce plagiarism and improve academic essay skills.